Political and legal use of ambiguity in Mende historical discourse - Murphy, William P.
This paper was originally written for the land, law and oral history session of the 1983 annual meeting of the American Society of Ethnohis tory.
AR/MISR/33/2/4
English
Shelf no. 1.
Keywords: Culture and law; Civilization \H istory